2013
DOI: 10.3382/ps.2012-02646
|View full text |Cite
|
Sign up to set email alerts
|

Pathological changes associated with white striping in broiler breast muscles

Abstract: White striping is a condition in broiler chickens characterized grossly by the occurrence of white striations, seen parallel to the direction of muscle fibers, on broiler breast fillets and thighs. Based on visual evaluation of the intensity of white striping, breast fillets can be categorized into normal (NORM), moderate (MOD), and severe (SEV) categories. This study was undertaken to evaluate the details of changes in histology as well as proximate composition occurring in the fillets with respect to the 3 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
158
2
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(198 citation statements)
references
References 31 publications
25
158
2
6
Order By: Relevance
“…Severe white-striped meat showed lower myofibrillar protein concentration at almost all molecular weights (Figure 3). Degeneration of myofibrils (Kuttappan et al, 2013a;Petracci et al, 2013c;Sihvo et al, 2013), which coincided with an increase in the levels of some serum enzymes like creatine kinase and alanine transaminase (Kuttappan et al, 2013b), can explain the disparity in the pattern of sarcoplasmic and myofibrillar proteins as well as the differences in the concentration for both types of proteins between normal and severe white-striped fillets.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Severe white-striped meat showed lower myofibrillar protein concentration at almost all molecular weights (Figure 3). Degeneration of myofibrils (Kuttappan et al, 2013a;Petracci et al, 2013c;Sihvo et al, 2013), which coincided with an increase in the levels of some serum enzymes like creatine kinase and alanine transaminase (Kuttappan et al, 2013b), can explain the disparity in the pattern of sarcoplasmic and myofibrillar proteins as well as the differences in the concentration for both types of proteins between normal and severe white-striped fillets.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have pointed out the presence of different histological changes in the breast of modern chicken hybrids like increased eosinophilia, floccular/vacuolar degeneration and lysis of fibers, mild mineralisation, occasional regeneration (nuclear rowing and multinucleated cells), mononuclear cell infiltration, lipidosis and interstitial inflammation and fibrosis (Kuttappan et al, 2013a;Petracci et al, 2013c;Sihvo et al, 2013). Hence, these modifications explain the increase of intramuscular lipids (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, several studies have shown that breast muscle fibres of fastgrowing strains showed a shift towards glycolytic metabolism and are characterised by a larger diameter, lower capillaryto-fibre ratio, greater intercapillary distance and lower rate of protein degradation compared with unselected breeds (Sosnicki and Wilson, 1991;Mahon, 1999;Schreurs, 2000). All these changes have contributed to the appearance of different structural and metabolic abnormalities within muscle that are usually accompanied by myodegeneration and subsequent regeneration (Dransfield and Sosnicki, 1999;Sandercock et al, 2009;Petracci and Cavani, 2012) Recently, abnormalities have also been observed in breast muscles characterised by degenerative myofibrillar proteins that impair the functionality of cell membranes (Kuttappan et al, 2013a;Sihvo et al, 2014). This myodegeneration can be explained by the increased rate of growth of muscles, which exceeds the physiologically sustainable growth rate, leading to muscle damage (Wilson, 1990;Mahon, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Badane mięśnie cechuje twardość (potoczna nazwa tej miopatii -"drewniana pierś"), a w obrazie histopatologicznym stwierdza się liczne ogniska degeneracji i regeneracji włókien mięśniowych oraz białe prążkowanie spowodowane nagromadzeniem tkanki łącznej i limfocytów (52). W innym badaniu wykazano dodatkowo zmienną wielkość włókien mięśniowych, łagodną mineralizację tkanki, zapalenie i lipidozę (35).…”
unclassified